A novel high-strength Al-La-Mg-Mn alloy for selective laser melting. (20th February 2023) - Zhang, Xinkui; Li, Liejun; Wang, Zhi; Peng, Hanlin; Gao, Jixiang; Peng, Zhengwu
Highlights: A novel Al-La-Mg-Mn alloy was designed for selective laser melting. The formation of hierarchical intermetallic was investigated. The SLM-printed Al-La-Mg-Mn alloy exhibits an excellent tensile strength and appreciable failure strain. The effect of hierarchical intermetallic on ductility was investigated. Abstract: Developing high-strength Al-(La, Ce) alloys for additive manufacturing (AM) would entail considerable economic benefits. In this work, a novel near-eutectic Al-La alloy containing 5.50 wt.% Mg and 0.60 wt.% Mn was designed and fabricated via selective laser melting (SLM). Submicron Al11 La3 intermetallics with 3D continuous cellular-dendritic and granular morphologies were observed at the interior and boundary of the melt pool, respectively. Interestingly, these intermetallics are hierarchical and contained numerous Al6 Mn and Mg2 Si secondary nanoprecipitates. The as-fabricated alloy exhibited a tensile yield strength (YS) of 334 MPa and ultimate tensile strength (UTS) of 588 MPa at room temperature, which is the highest UTS reported for Al-(La, Ce) alloys with an appreciable failure strain of ∼6.4%. The 3D continuous cellular dendritic intermetallic and high Mg content afford significant strengthening and work hardening ability. In addition, the hierarchical feature of the intermetallics generated additional microcracks to coordinate the deformation.